2016
DOI: 10.1038/jhh.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hypertension on leukocyte telomere length: a systematic review and meta-analysis of human studies

Abstract: Shortened leukocyte telomere length (LTL) is a novel biomarker for age and age-related diseases. Several epidemiological studies have examined the association between telomere length in surrogate tissues (for example, blood cells) and hypertension, and meanwhile the majority of studies reported an association some individual studies do not. We carried out a systematic review and meta-analysis to address the hypothesis that, in humans, telomere length is related with hypertension. Searches were conducted in Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 53 publications
5
42
0
2
Order By: Relevance
“…Hypertension is a cardiovascular risk factor 42 , and our results also found an increase in the prevalence of CVD in hypertensive people (data not shown), which may affect the association. In addition, the LTL of non-hypertensive patients in the present study was longer than that of hypertensive patients, which was consistent with the results of a previous meta-analysis 43 , possibly due to the shortening of the telomere length of endothelial progenitor cells in hypertensive patients 44 . The presence of high blood pressure may have affected the association, but the specific reason is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Hypertension is a cardiovascular risk factor 42 , and our results also found an increase in the prevalence of CVD in hypertensive people (data not shown), which may affect the association. In addition, the LTL of non-hypertensive patients in the present study was longer than that of hypertensive patients, which was consistent with the results of a previous meta-analysis 43 , possibly due to the shortening of the telomere length of endothelial progenitor cells in hypertensive patients 44 . The presence of high blood pressure may have affected the association, but the specific reason is unknown.…”
Section: Discussionsupporting
confidence: 93%
“…Another possible source of heterogeneity might be the inter-laboratory technical variation of quantitative PCR (qPCR) to measure relative telomere length, which tend to yield higher variability than Southern blotting ( Aviv et al, 2011 , Gardner et al, 2014 ), although a study by Martin-Ruiz et al suggested that both techniques show comparable intra- and inter-assay inconsistencies ( Martin-Ruiz et al, 2015 ). Previous meta-analyses on cross-sectional associations between other lifestyle-related factors such as hypertension or obesity and leukocyte telomere length also reported high heterogeneity ( Mundstock et al, 2015 , Tellechea and Pirola, 2016 ), which may indicate the need to address methodological problem in telomere association study that should involve standardisation of qPCR and Southern blotting protocols ( Martin-Ruiz et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shorter telomere length, a cellular marker for biological age, was associated with a higher metabolic risk profiles, which remains unfavorable even after a period of 6 years[16]. Accumulating evidences demonstrated that shortened leukocyte telomere length had a significant association with stroke, myocardial infarction, and type 2 diabetes mellitus[1719]. However, it is unclear whether gender differences existed in the association between MetS and leukocyte telomere length.…”
Section: Introductionmentioning
confidence: 99%